Abdul Hadi"s translations of Ahmad Raza: An internal logics approach - Rafudeen, Auwais (HTS teologiese studies, 2023)
This article employs an internal logics approach, developed in a recent work by Sher Ali Tareen, to the study of the Barelwi school in South Africa. This approach ties metaphysics to practice. Specifically, the article addresses some works of the school’s founder, Ahmad Raza Khan, as translated by South African Islamic scholar Abdul Hadi Qadiri, in the light of this approach. It then extrapolates the insights of this approach to a recent article by Sepetla Molapo, which highlights the importance of appreciating the metaphysical role of ancestors in any academic approach to understanding traditional African worldviews and African self-concept. Taken together, the article suggests that the internal logics approach is helpful in bringing to the surface the crucial, but often obscured, metaphysical presuppositions concerning the nature of time-presuppositions that inform not only the worldview of the object being studied, but, equally, the often different ones that shape the perspective of the researcher.Contribution: This article wishes to underscore the importance of metaphysical considerations in the study of religion, advocating an approach that highlights such considerations and examining some of its broader academic implications. While it specifically focuses on a theological contestation in Islam, it extends the implications of this contestation to the academic study of traditional African worldviews and to world religions more generally.